Alumina-graphene hybrid filled epoxy composite: Quantitative validation and enhanced thermal conductivity. (15th December 2017) - Akhtar, M. Wasim; Lee, Yun Seon; Yoo, Dong Jin; Kim, Jong Seok
Abstract: Alumina-graphene hybrid fillers ( Gr -Al2 O3 ) were synthesized and added to the epoxy matrix to improve thermal properties of the epoxy composite. The alumina particles were surface modified with silane coupling agents like 3-Aminopropyl triethoxysilane ( A -Al2 O3 ). 3-Glycidyloxypropyl trimethoxysilane (GPTMS) was used for the surface modification of the graphene (G-Graphene). These modifications on the filler surface help to develop the interface between the fillers and the epoxy matrix, which might help to form the effective 3D thermal conductive networks. The generation of these 3D networks facilitated in reducing the Kapitza resistance and increases the transportation of phonons in the matrix, Furthermore; it improved the integral procedure decomposition temperature (IPDT) and activation energy (Ea ) of the composite. Alumina-graphene hybrid filled epoxy composite ( hAG -Epoxy) with 50 vol% of hybrid filler ( Gr -Al2 O3 ) expressed the considerable improvement in in-plane thermal conductivity and IPDT by ∼8.4 and ∼3.1 folds in comparison with neat epoxy, respectively. The significant improvement in thermal conductivity was related to the generation of effective 3D thermal conductive pathways formed by 2D graphene and 1D alumina in the composite. Graphical abstract: Highlights: Hybridization of alumina and graphene is carried through functionalization with silane coupling agents. Surface modifications helps appropriate bonding between fillers and further helps in developing good interface with epoxy matrix, decrease thermal interface resistance and increase phonon transportation. The thermal conductivity is enhanced upto to 1.67 W m −1 . K −1, which is ∼8 fold with compare to neat epoxy. The experiments is also compare with Maxwell and Bruggeman's model for effective thermal conductivity. The hybrid filler improves the thermal conductivity and thermal stability of the epoxy composite.